1878 Reverend Robert Troupe Deed - Reverend Robert Troup (Valdosta State University Archives and Special Collections, 2026, 1878)
On January 11, 1877, W. H. and T. S. McKey sold six acres of land to Robert Troup for the sum of sixty dollars. The property was located in Lowndes County, Georgia, in the 12th District, and was described as part of Lot No. 1. The deed provides measurements of the tract, noting that it extends approximately 140 yards from the commencement point on the western boundary and 200 yards northward, defining the six-acre parcel. The sellers conveyed the land to Robert Troup, his heirs and assigns forever, together with all rights and appurtenances (any right, privilege, or improvement permanently attached to the land that automatically transfers to the new owner (such as easements, shared driveways, or mineral rights) belonging to the property. They also warranted that they held clear title to the land and agreed to warrant and defend the title against any future claims. The deed was signed and sealed by W. H. and T. S. McKey at the Ordinary of Lowndes County. Although the transaction occurred on January 11, 1877, it was not officially recorded until September 10, 1878.
1 JPEG
Keywords: River Hill Missionary Baptist Church (Valdosta, Ga.); Baptist churches; Church buildings